"Gauze Technique" in the Treatment of the Fungus Ball of the Maxillary Sinus: A Technique as Simple as It Is Effective. (19th December 2016) - Garofalo, Pietro; Griffa, Alessandro; Dumas, Georges; Perottino, Flavio
Abstract : Fungus ball of maxillary sinus generally affects immunocompetent and nonatopic subjects. Although endoscopic removal is the current gold standard treatment, removal is at times difficult due to an accumulation of fungal elements in the anterior ad inferior recesses. Aim . To present our experience of maxillary fungus ball treated by the "gauze technique" that avoids these removal difficulties. Materials and Methods . A retrospective, cross-sectional, and descriptive study of 25 patients affected by maxillary fungus ball was carried out: 19 were treated by the "gauze technique" and 6 were treated without "gauze technique." Results . A comparison was made between the two groups for surgery procedure time, length of hospitalization, time from surgery to nasal unpacking, complications, and postsurgical patient satisfaction. The only statistically significant difference observed was a shorter surgical procedure time (p < 0.05 ) for the "gauze technique." Conclusions . The data obtained in this study demonstrated that the "gauze technique" is a safe, simple, and quick technique, able to reduce surgery procedure time whilst providing excellent functional outcomes and patient satisfaction.